Features of callusogenesis of soybean Glycine max (L.) Merr. samples with different photoperiodic response - Авксентьєва, О. А.; Васильченко, М. С. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The paper presents the results of a study of the frequency of primary callus formation of different explants, growth response and morphological characteristics of callus primary and passaged cultures of soybean samples with different photoperiodic sensitivity. It has been showed that short-day soybean samples are more efficiently introduced into the culture in vitro, and their callus tissues are characterized by more intensive growth compared to callus of photoperiodic insensitive plants. It is assumed that the genes of soybean maturing controlling photoperiodic sensitivity of plants in vivo are involved in processes of predetermination of callus formation in conditions in vitro.